Hajj across empires: Pilgrimage and political culture after the Mughals, 1739-1857 - Choudhury, Rishad, 1984- (New York, USA: Cambridge University Press, 2023)
"A highly original new history of Muslim political culture across the Indian Ocean from 1739 to 1857. Examining South Asian connections with the Middle East, Rishad Choudhury draws on research in multilingual sources and archives to reveal the imperial entanglements of the hajj pilgrimage to Mecca"--
Introduction: Hajj in the Crisis of Empire -- PART I. DEPARTURES: EXPERIENCES AND EXCHANGES IN THE INDIAN OCEAN: 1. Pilgrim Passages -- 2. The Hajj Bazaar Economy -- PART II. CROSSINGS: IDEOLOGIES AND INSTITUTIONS ACROSS EMPIRES: 3. The ʻUlama on Hajj -- 4. Hindi Sufis and the Hajj -- PART III. RETURNS: STATES BETWEEN HOME AND THE HARAMAIN: 5. The Company Raj and the Hajjis -- 6. Routes of the Muslim State -- 7. Faqirs and Fanatics, or, Reconfiguring Pilgrimage and Political Culture -- Conclusion: The Hajj and the Ends of the Mughal World.
Includes bibliographical references and index.
Keywords: Muslim pilgrims and pilgrimages -- Saudi Arabia -- Mecca -- History; Religion; Mughal Empire -- Civilization -- 18th century; Mughal Empire -- Civilization -- 19th century